Different effect of hydroxyapatite granules in posterolateral spinal fusion in New Zealand white rabbit: a preliminary result - Buyong, Zunariah; Zakaria@Mohamad, Zamzuri; Zulkifly, Ahmad Hafiz; Khalid, Kamarul Ariffin (2009)
The aim of this experimental study is to compare fusion status at lumbar intertransverse processes between implantation with hydroxyapatite (HA) granules alone, HA granules mixed with autologous platelet rich plasma (HA-PRP) and autograft. Twenty-four New Zealand white rabbits were used. The rabbits were randomized into two groups of 12 rabbits each based on the graft materials used. All the rabbits underwent single level bilateral lumbar fusion. One side of the animals was implanted with either HA alone or HA mixed with PRP. While the contra lateral sides were implanted with autograft, and served as the control. Four of the animals from each group were killed at 6, 12 and 16 weeks for undecalcified histological and radiological assessments. Preliminary results showed the control group with autograft healed with a good fusion mass. Interestingly, HA granules only group healed with better bone formation than HA-PRP.